SATURN: An Introduction to the Internet of Materials. - Arora, Nivedita; Starner, Thad; Abowd, Gregory D. (Communications of the ACM, 2020)
We envision a new generation of computation devices, computational materials, which are self-sustainable, cheaply manufactured at scale and exhibit form factors that are easily incorporated into everyday environments. These materials can enable ordinary objects such as walls, carpet, furniture, jewelry, and cups to do computational things without looking like today's computational devices. Self-powered Audio Triboelectric Ultra-thin Rollable Nanogenerator (SATURN) is an early example of a computational material that can sense vibration, such as sound. SATURN can be manufactured from inexpensive components, is flexible so that it can be integrated into many different surfaces, and powers itself through the sound or vibration it is sensing. Using radio backscatter, we demonstrate that SATURN's sensed data is passively transmitted to remote computers, alleviating the need for batteries or any wired power for the material itself. The proliferation of these types of computational materials ushers an era of Internet of Materials, further blurring the distinction between the physical and digital worlds.